First report of SSR identification in the new improved genome assembly of Duck (ZJU1.0) - Jayakumar Sivalingam; Chaudhari Mahesh Vishwas; Athe Rajendra Prasad; Sajeed Mohd; Bachamolla Shivani; Satya Pal Yadav; T.K. Bhattacharya; M. Balakrishnan (Journal of Livestock Biodiversity, 2025)
Ducks (Anas platyrhynchos) were among the earliest domesticated fowls in the world. The Illumina-based genome assembly of the duck, BGI1.0 reference (GCA_000355885.1), was produced by Huang et al (2013), but recently Li et al (2021) produced a new duck genome assembly (ZJU1.0) with overall improvement compared to BGI1.0 duck genome, the previous Sanger-based zebra finch, and is comparable to the latest version of chicken and VGP zebra finch genomes. ZJUI1.0 duck genome has 62-fold improvement of scaffold continuity and assembled majorities of micro chromosomes that were all unmapped in the BGI1.0 genome. In the present study, the new Duck genome assembly (ZJU1.0)was downloaded from the NCBI and was used for identification of SSRs using MISA software. A total number of 7,03,449 SSRs were identified in the Mono-, di-, tri-, tetra-, penta-, and hexanucleotide repeats. Without taking into consideration of the mononucleotide repeats, our catalogue provides the first duck SSR reference based on ZJU1.0 genome including 183,406SSR loci with motifs of 2-6 bp at 163 SSRs/Mb density. Without considering mononucleotide repeats, we observed that dinucleotide repeats were most abundant. The correlation between repeat motifs and SSR frequency was negative in our study in accordance with trend observed by Fan et al., 2018 except tetranucleotide repeats.